Beberapa Kendala dalam Penyelesaian Status Hukum Tanah Bekas Swapraja di Daerah Istimewa Yogyakarta - Ni'matul Huda (Jurnal Hukum IUS QUIA IUSTUM, 2000)
Pertaining to the 'lex posteriori derogat legi inferioh principle', the issuance of the Act No.5,1960 of UUPA (the Basic Principle of Agrarian Law) seems different It results that theauthority of the Yogyakarta Special Territory Province having its own nghts to arrange land affairs as an autonomy authority based on the Act No. 3,1950, becomes nullified. Despite the reality, the resolution ofthe fourth Dictum letter 'a'of the Basic Principle of AgrarianLaw (UUPA) is bias. It states that since the Act iseffective, rights and authority of the land and water of autonomous region or ex-autonomous region prevailing atthe time become removed, and those change into State ownership since then. The arrangement of the fourth Dictum lettera will be settled in the forms of government regulation, and the government regulation it self has not been issued yet In terms of its legal status, the ex-autonomous land in Yogyakarta Special Territory Province is unclear.